Engineering education system between Indonesian Vocational School and Japanese KOSEN. Issue 1 (May 2020) - Siswanto, A P; Budiyono,; Kasai, H; Fujiwara, S; Mizuno, Y
Abstract: International partnership has become an emerging issue in which due to globalization goals, the needs of having collaboration between countries are inevitable. Cross-continents collaborations are encouraged; however, having partners with similar cultural background is seen more beneficial. This article aims to review challenges on programme development of Vocational Education between Indonesian and Japan. Vocational Education in Indonesia has been well established for decades where students are trained in 3-year education of Vocational High School then continue to 3-year education of Vocational School at the University. Curriculum is set to be more giving practical training which can enhance skills of students in problem solving. Moreover, KOSEN is one of distinctive education systems in Japan which is an abbreviation of Japanese form "koku-ritsu-kou-gyou-KOU-tou-SEN-mon-gak-kou" which is translated as National Institute of Technology. It offers 5-year education after Junior High School which provides training and skills development for students. Programme development of KOSEN and Indonesian Vocational Education are seen to be feasible for being implemented further which can deliver more skilful graduates. Combination of skills and cultural side of graduates are expected to be positively influencing their working ethics. Comprehensive capability of graduates is linear to their competency which also increases their employability.